Succulent plants - Griffiths, Howard; Males, Jamie (Current biology, 2017)
The peculiar morphologies of succulent plants have been variously considered as grotesque monstrosities and exotic curiosities, but succulents have always been perceived as unique. The succulent syndrome is considered to be one of the most remarkable examples of convergent evolution across the plant kingdom. Common to all succulents is the presence of large cells for water storage. However, cellular succulence can occur in any vegetative plant organ, with the level of succulence in roots, stems, and leaves being subject to a certain degree of evolutionary coordination. Furthermore, cellular succulence scales up to morphological succulence according to various anatomical schemes that confer contrasting functional characteristics. This means that succulence is associated with a broad range of ecophysiological strategies and occurs in plants that have evolved in many different environments. In this Primer, Griffiths and Males provide an introduction to the different structural and functional properties of the succulent syndrome, and define different categories of succulent plants.